Smart Car Parking System based on RFID - V, Manideep Goud; B, Srinivas Rao (International Journal of Computer Sciences and Engineering, 2019)
From the few years’ people of cities has persevered to grow at a fast way. The most important purpose of occurrence in increasing international locations like Morocco is the agricultural migration. In truth, rural children are more and more attracted by the modern-day manner of lifestyles and the opportunity of employ presented with the aid of cities. This boom in populace density has a massive wide variety of terrible outcomes on the nice of life in the metropolis. To solve the parking issue, here presents the area and development of a clever parking gadget the use of the modern-day technology. Our device makes use of an adaptable and hybrid self-corporation set of rules for wi-fi sensors that adapts to all of car parkings present within the city, and offers a higher control of the power utilization during the wi-fi verbal exchange to growth the life of the sensor nodes.